Fossil grebes from the Truckee Formation (Miocene) of Nevada and a new phylogenetic analysis of Podicipediformes (Aves). (27th April 2013) - Ksepka, Daniel T.; Balanoff, Amy M.; Bell, Michael A.; Houseman, Michel D.; Angielczyk, Kenneth
<x xml:space="preserve">Abstract</x> Podicipediformes is a cosmopolitan clade of foot‐propelled diving birds that, despite inhabiting marine and lacustrine environments, have a poor fossil record. In this contribution, we describe three new grebe fossils from the diatomite beds of the Late Miocene Truckee Formation (10.2 ± 0.2 Ma) of Nevada (USA). Two postcranial skeletons and an associated set of wing elements indicate that at least two distinct grebe species occupied the large, shallow Lake Truckee during the Miocene. Phylogenetic analysis of morphological data supports a basal divergence between a clade uniting the dabchicks (Tachybaptus, Limnodytes, Poliocephalus) and a clade uniting Podilymbus, Rollandia, Podiceps and Aechmophorus. Missing data, combined with a paucity of informative skeletal characters, make it difficult to place the Truckee grebes within either of these major clades. Given the weak projection of the cnemial crests compared with extant grebes, it also remains plausible that these specimens represent stem lineage grebes. Although more material is needed to resolve the phylogenetic position of the Truckee grebes, our analysis offers insight into the tempo of grebe evolution by placing the Miocene taxon Thiornis sociata within the dabchick clade. Thiornis sociata provides a minimum age calibration of 8.7 Ma for the basal divergence among dabchicks. Based on the recovery of a nonmonophyletic Tachybaptus and placement of the Western Hemisphere 'Tachybaptus' dominicus as the basal member of the otherwise exclusively Eastern Hemisphere dabchick clade, we resurrect the genus Limnodytes for this extant species (Limnodytes dominicus). Our results also nest the large, long‐necked Aechmophorus grebes within the genus Podiceps, as the sister taxon to Podiceps major.